2000
DOI: 10.1053/rapm.2000.7624
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia after peripheral nerve block for podiatric surgery: Clinical efficacy and chemical stability of lidocaine alone versus lidocaine plus ketorolac

Abstract: The addition of ketorolac to lidocaine for ankle block contributed to longer duration and better quality analgesia after foot surgery compared with plain 1.73% lidocaine or 1.73% lidocaine plus intravenous ketorolac. The ethanol vehicle is unlikely responsible for the analgesic effects of ketorolac. Ketorolac retains its chemical stability when placed in local solutions of lidocaine or bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
(16 reference statements)
1
33
0
2
Order By: Relevance
“…These results are in agreement with those obtained by GAUMANN et al 7 using 1% lidocaine containing either clonidine (150 mg/ml) or epinephrine (200 mg/ml) for brachial plexus block in patients undergoing elective surgery of the hand or forearm when recovery of sensory block was not different between the groups, while intraoperative pain was not significantly experienced during procedure. REINHART et al 17 , using a lower concentration of clonidine (10 mg/ml) with 1.73% lidocaine for peripheral nerve block, have presented that duration of this anaesthesia was significantly longer than anaesthesia obtained with plain lidocaine (1.73%).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These results are in agreement with those obtained by GAUMANN et al 7 using 1% lidocaine containing either clonidine (150 mg/ml) or epinephrine (200 mg/ml) for brachial plexus block in patients undergoing elective surgery of the hand or forearm when recovery of sensory block was not different between the groups, while intraoperative pain was not significantly experienced during procedure. REINHART et al 17 , using a lower concentration of clonidine (10 mg/ml) with 1.73% lidocaine for peripheral nerve block, have presented that duration of this anaesthesia was significantly longer than anaesthesia obtained with plain lidocaine (1.73%).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have been carried out using different concentrations of clonidine for the enhancement of epidural anaesthesia 14 , brachial plexus anaesthesia 3,7 and anaesthesia of peripheral nerves 15,17 . These studies have shown that the effective concentrations of clonidine, without significant side effects, were 150 mg/ml 7 , 90 mg/ml 3 , 30 mg/ml 3 , 10 mg/ml 17 , 5 mg/ ml 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The similar effect of clonidine was also seen during lidocaine-induced intraoral block anaesthesia 2 . Clonidine is commonly injected with local anaesthetics to extend the duration of peripheral nerve blocks 1,6,20 , although the mechanism of this effect is not certain 1,23 .…”
Section: Discussionmentioning
confidence: 99%